Body armor suit usage in downhill cycling: a guard that induces disaster - Mohd Nor, Mohd Hanis; Che Mohamed, Siti Kamariah; Kamarulzaman, Mohd Nazli (John Wiley & Sons Ltd, 2018)
Introduction: Downhill mountain bike is considered as an extreme sport. The most commonly injured body sites were the lower leg (27%) followed by the forearm(25%). Most frequent injury types were abrasions (64%) and contusions (56%).Main causes of injury reported by the riders were riding errors (72%) and bad trail conditions (31%). Renal injury is rare but may happen if there is high velocity impact. We report a case of grade 4 renal injury in a patient who is a cyclist. Case Report: An 18 year-old girl who is a professional athlete was participating in a downhill mountain bike tournament in Sabah and had a fall while riding down-hill. She was wearing a body armor suit during the incident. She had right loin pain but no obvious loin bruises or hema-toma were noted. The patient had hema-turia while she was warded. In view of gross hematuria, renal protocol computed tomography scan was performed. The imaging showed a grade IV right renal injury. The hematuria subsided after2 days and her pain gradually improved. Blood investigations including renal profile were normal and urine test was negative. When we reviewed the video of the incident we concluded that spontaneous disassembly of body armor caused the flank injury in this patient as the bike and her body had fallen in different directions. Conclusion: Grade 4 renal injury in mountain bike accidents is rare but can still happen. Increased awareness and development of protective equipment in this area need to be improved to ensure safety in this extreme sport.